DEMOGRAPHIC CHANGES: A CHALLENGE TO THE DECOLONIZATION OF KASHMIR - Ali, Sultan Ahmed (PEOPLE: International Journal of Social Sciences, 2020)
Decolonization of Kashmir is one of the oldest agenda at the United Nations. The world has witnessed a successful wave of decolonization in the second half of the 20th century. The spirit of decolonization was to transfer power to the indigenous population of a region by taking the doctrine of self-determination and political equality as its guiding principles. Recent unilateral acts by the BJP government to revoke the constitutional protection reserved for Indian Occupied Kashmir (IOK) are intended for relocating the populous boundaries through demographic changes. India drafted a project in 2015 aiming to build accommodations for thousands of Hindu residing in different parts of India in IOK. These demographic changes will harm the spirit of the right of self-determination – for any plebiscite being held in future – thereby leading Kashmir towards neo-colonialism. This paper highlights the politico-legal aspects of the concept of plebiscite, unveiled the neo-colonial ideology of the current Indian government and exposed the Indian mala fide intentions of demographic changes in the revocation of the special status of Indian Occupied Kashmir. These underlining realities will be discussed in an attempt to argue how current demographic changes have become the gravest challenge to the decolonization of Kashmir. Deliberate and illegal demographic changes in Kashmir, its impacts on the existing UN resolutions, perpetual increase in human rights violations and other possible challenges to the decolonization of Kashmir are the major areas that are addressed in this paper.